Emerging Victims in Contemporary Drugs Policing - Marshall, Hannah (The British journal of criminology, 2024)
Recent shifts in UK policy have seen certain populations, who were predominantly viewed as offenders due to their involvement in drug offences, increasingly recognized as victims of exploitation. Drawing on qualitative data from three studies, this article interrogates how this trend is playing out within contemporary drugs policing, focussing on officers’ responses to people affected by: drug addiction, child criminal exploitation and ‘cuckooing’. It examines the tensions that arise as these three categories of emergent drug victims conflict with officers’ normative expectations of victimhood, perceptions of their role as police and existing operational strategies. It also reveals officers’ attempts to (re)gain ontological security by policing the boundaries of victimhood and re-focussing on new categories of offender.